2016
DOI: 10.1105/tpc.15.00771
|View full text |Cite
|
Sign up to set email alerts
|

The RNA Polymerase II C-Terminal Domain Phosphatase-Like Protein FIERY2/CPL1 Interacts with eIF4AIII and Is Essential for Nonsense-Mediated mRNA Decay in Arabidopsis

Abstract: Nonsense-mediated decay (NMD) is a posttranscriptional surveillance mechanism in eukaryotes that recognizes and degrades transcripts with premature translation-termination codons. The RNA polymerase II C-terminal domain phosphatase-like protein FIERY2 (FRY2; also known as C-TERMINAL DOMAIN PHOSPHATASE-LIKE1 [CPL1]) plays multiple roles in RNA processing in Arabidopsis thaliana. Here, we found that FRY2/CPL1 interacts with two NMD factors, eIF4AIII and UPF3, and is involved in the dephosphorylation of eIF4AIII.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 55 publications
(71 reference statements)
0
17
0
1
Order By: Relevance
“…In addition to this function, HWS has also been reported to affect general plant and organ growth (González-Carranza et al, 2007;Yu et al, 2015). Further, it is reminiscent of relatively weak, pleiotropic defects in other miRNA factors like CPL1 (Manavella et al, 2012;Jeong et al, 2013;Cui et al, 2016) and suggests that HWS may affect growth processes via the miRNA pathway, either through direct involvement in miRNA function, stability or even degradation, or upstream of miRNA-related processes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this function, HWS has also been reported to affect general plant and organ growth (González-Carranza et al, 2007;Yu et al, 2015). Further, it is reminiscent of relatively weak, pleiotropic defects in other miRNA factors like CPL1 (Manavella et al, 2012;Jeong et al, 2013;Cui et al, 2016) and suggests that HWS may affect growth processes via the miRNA pathway, either through direct involvement in miRNA function, stability or even degradation, or upstream of miRNA-related processes.…”
Section: Discussionmentioning
confidence: 99%
“…A 2015 study in a recreation and sport facility found increased sales of healthy items and reduced sales of unhealthy items after implementation of TLLs (9). An online workplace lunch order and a food lab study also found that TLLs improved food choices (10,11). However, there is no consensus on whether TLLs are an appropriate way to encourage healthy eating in college students (12), and there are no qualitative studies on experiences with TLLs.…”
Section: Introductionmentioning
confidence: 99%
“…This reporter-gene-specific effect by the cpl1 mutation explains why mutations in CPL1/FRY2 as well as in HOS5/RCF3 encoding a binding partner of CPL1 are repeatedly identified in LUC reporter gene-based forward genetic screening, and why there are discrepancies between LUC expression level and endogenous counterpart in cpl1/fry2. Because LUC mRNA has a short half-life in the plant cell 1,11 , the likely mechanism is LUC mRNA but not endogenous counterpart being a target of CPL1dependent RNA decay pathway 10 . This observation suggests that we need to be cautious about the impact of cpl1 on synthetic phenotype produced by artificial transgenes, because cpl1 may produce phenotype by specifically affecting the level of transgene expression.…”
mentioning
confidence: 99%
“…The first reported evidence that CPL1 affects state of LUC reporter mRNA was that a cpl1 mutant showed higher capping efficiency and altered polyadenylation site of LUC mRNA. Another study demonstrated that CPL1/FRY2 regulate RNA decay pathway of abnormal transcripts, such as transcripts that retains one or more introns (Cui et al, 2016).…”
mentioning
confidence: 99%
See 1 more Smart Citation